Banking in the Digital Era: A Novel Supply Chain Finance Model to Enhance SME Financial Inclusion - Syed Amir Ali; Dr. Syed Muhammad Salman (Indus Journal of Social Sciences, 2025)
Fintech innovation, Supply Chain Finance, and Stakeholder Collaboration are reshaping access to finance and enabling sustainable growth in banking. New access to financial products is now crucial to bridge liquidity gaps, improve the provision of capital, and enhance financial inclusion, particularly for Small and Medium-sized Enterprises (SMEs). In spite of SMEs contributing significantly to economies worldwide, they mostly endure poor financing due to stringent credit terms and collateral limitations. This study examines the role of Fintech adoption, supply chain financing, and stakeholder coordination in enhancing financial access and its impact on SME finance growth in the banking sector. Through the use of a quantitative approach, the study utilizes Structural Equation Modeling (SEM) in its empirical testing of direct and indirect relationships between the most applicable financial enablers and SME finance. Data were collected from banking experts, providers of financial services, fintech experts, and stakeholders of SMEs. It recognizes that Fintech innovations, financial institution strategic collaboration, and supply chain finance are crucial in enabling access to finance, hence promoting SME finance growth. Out of all the independent variables, Fintech adoption contributes the most, once again demonstrating that it is at the forefront of contemporary banking activities. In addition, the statistical function of access to finance as a mediator is material, as it indicates the necessity for a permanent digital financial system. This research adds to the literature in the sense that it brings financial innovations in supply chain and digital finance together under a single canopy of the whole banking sector with special focus being laid on how banking institutions can adopt technologically driven financial solutions. The research provides implications for practical usage to Islamic and conventional banks by calling for intensified financing infrastructure digitalization, policy measures, and social financial institutions to facilitate the reduction of SMEs' finance gap. Second, the theoretical framework put forth gives a conceptual model that could further be studied on the finance sector contribution from digital transformation by following an inclusive, efficient, and sustainable banking sector.